2012
DOI: 10.1371/journal.pone.0039704
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequencing and Comparative Analysis of Saccharina japonica (Laminariales, Phaeophyceae) under Blue Light Induction

Abstract: BackgroundLight has significant effect on the growth and development of Saccharina japonica, but there are limited reports on blue light mediated physiological responses and molecular mechanism. In this study, high-throughput paired-end RNA-sequencing (RNA-Seq) technology was applied to transcriptomes of S. japonica exposed to blue light and darkness, respectively. Comparative analysis of gene expression was designed to correlate the effect of blue light and physiological mechanisms on the molecular level.Prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 95 publications
2
48
0
Order By: Relevance
“…Instead of phytochrome, stramenopiles possess their own blue light photoreceptor, aureochrome (Takahashi et al 2007). The transcriptome of Saccharina japonica sporophytes under blue light was characterized by Deng et al (2012), while differential gene expression under blue and red light was studied by Wang et al (2013). The results indicated that the number of differentially expressed genes was significantly higher under red light conditions compared to blue light.…”
Section: Light Quality and Identity Of Photoreceptorsmentioning
confidence: 99%
“…Instead of phytochrome, stramenopiles possess their own blue light photoreceptor, aureochrome (Takahashi et al 2007). The transcriptome of Saccharina japonica sporophytes under blue light was characterized by Deng et al (2012), while differential gene expression under blue and red light was studied by Wang et al (2013). The results indicated that the number of differentially expressed genes was significantly higher under red light conditions compared to blue light.…”
Section: Light Quality and Identity Of Photoreceptorsmentioning
confidence: 99%
“…Alternatively, the transcriptome analysis based on the next generation sequencing (NGS) is more attractive in identifying the expression gene for its characteristics of cost-efficient, high throughput and rapidness. NGS, including the Roche/454 Genome Sequencer FLX Instrument, the ABI SOLiD System and the Illumina Genome Analyser, was a powerful tool and was untilized in many researching areas, including re-sequencing, micro-RNA expression profiling, DNA methylation, especially de novo transcriptome sequencing for non-model organisms [5-13]. Recently, based on the NGS technology, the transcriptome of many species such as chestnut [9], coral larval [5], sweetpotato [11], ginseng root [10], chickpea [12] and saccharina japonica [13] had been analyzed, which has accelerated our understanding of the complexity of expression, regulation and networks of gene in model and non-model organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The fragments per kilo bases per million reads (FPKM) were used to evaluate expressed values and quantify transcript levels, which normalizes and eliminates the influence of gene length and sequencing depth in calculating gene expression, allowing for direct comparison of gene expression between different treatments [20]. Genes with an adjusted p-value < 0.05 was assigned as differentially expressed according to the reports of Deng et al [21]. For pathway enrichment analysis, all differentially expressed unigenes were submitted in the online KEGG Automatic Annotation Server (http://www.…”
Section: Transcriptome Analysismentioning
confidence: 99%